Serendipity-driven celebrity video hyperlinking - YANG, Shujun (Institutional Knowledge at Singapore Management University, 2016)
This demo showcases the utility of video hyperlinks with celebrities as the link anchors and their social circles as targets, aiming to help users quickly explore the aboutness of a celebrity by link traversal. Through content analysis, our system embeds hyperlinks into videos such that users can click-and-jump between celebrity faces in different videos to get-to-know their social circles. One peculiar feature is the ability of the system in providing links that maximize users' chance encounter, or serendipitous experience, beyond information need. Our system is enabled by two key components, name-face association and diversity-based ranking, for the aboutness and serendipity features respectively in hyperlinking. The former component assigns names video faces while mining celebrity social networks. The latter performs topic modeling so as to rank videos based on topic diversity.